Tanggung Jawab Komisaris Perusahaan Perseroan BUMN Ditinjau dari UU No 40 Tahun 2007 Tentang Perseroan Terbatas - Shafira Andiena Qoyyumi Permadi; Ariawan Ariawan (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
State-Owned Enterprises or SOEs, are business entities whose share ownership is mostly owned by the state and are also one of the business entities that support the country's economy. Apart from producing goods and/or services, the presence of SOEs can also be a means of employment for the workforce. In order to support the success of a business, BUMN has three important organs, namely the GMS, Directors and Commissioners. In Article 6 paragraph (2) of Law Number 19 of 2003 concerning State-Owned Enterprises it is said that